PENGARUH SENAM LANSIA TERHADAP TEKANAN DARAH PADA KOMUNITAS DAHLIA SENJA LIMO - Khairunnisa Aulia Jasmine (2022)
Background : Exercise is very good, especially for the elderly so that blood flow becomes smooth, one of the sports recommended for the elderly to prevent chronic diseases such as increased blood pressure is elderly exercise. In the elderly, the heart's power to pump is reduced. Elderly exercise can help increase the strength of the heart pump, so that blood flow can return smoothly. The objective of this research was to examine if exercise has an impact on the blood pressure of older residents of the Dahlia Senja Limo Community. Design : This research used a quasi-experimental approach with pre- and post-testing. Results : Before the elderly exercised, the average systolic blood pressure was 131.84 and diastolic was 85.92 mmHg. After the elderly exercised, the average systolic blood pressure was 130.66 and diastolic was 82.24. Based on the findings of the paired sample t-test between the pre-test and post-test group data, the p-value of 0.000 where the significance value = 0.000 < α = 0.05 shows that there is a significant difference between the average pre-test and post-test blood pressure in the experimental group. This research concludes that there is a correlation between exercise and blood pressure among the elderly in the Dahlia Senja Limo Community.